Physiological and anthropometric progression in an international oarsman: a 15-year case study - Bourgois, J. G.; Steyaert, A.; Boone, J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: In this case study, a world-class rower was followed over a period of 15 y in which he evolved from junior to professional athlete. Methods: An incremental exercise test and a 2000-m ergometer test were performed each year in the peak period of the season starting at the age of 16 y. In addition, the training logs of 1 y each as a junior and a senior rower were recorded and analyzed. Results: Maximal oxygen uptake (VO2max), maximal power output (Pmax), and power output at 4 mmol/L blood lactate concentration increased until the age of 27 and then stabilized at 30 y at 6.0 ± 0.2 L/min, 536 ± 15 W, and 404 ± 22 W, respectively. At the age of 27-28 y the rower also had a career-best 2000-m ergometer test (5'58?) and on-water performance with a 4th place at the Olympic Games (2008) in Beijing and World Championships (2009). At the age of 23 y, the rower trained a total of 6091 km in 48 wk. Of the total training time, 15.4% consisted of general training practices, 23.4% resistance training, and 61.2% specific rowing training. Conclusion: The on-water performance in the World Championships and Olympic Games corresponded closely to the evolution in the rower`s physiological profile and 2000-m ergometer performance. The long-term build-up program resulted in an increase in the physiological parameters up to the age of 27 y and resulted in a 4th position at the 2008 Olympic Games at a body mass of only 86 kg.